From Celebrity Fandom to Consuming Korean Product Brands: The Extending Lifestyle of 'Wannable' Fans in Jakarta - Raden Roro Nisrina Salma Hanifah; Dessy Kania (Jobmark: Journal of Branding and Marketing Communication, 2023)
The current phenomenon sees that South Korea's popular culture is growing, so it has so many fans scattered around the world, including in Indonesia. Many K-Pop fans in Indonesia will show a variety of behaviors shown by K-Pop fans so that they can be assessed the stages in which fans they are to their K-Pop artists. Wannable itself is a fandom name of the South Korean group called Wanna One and Wanna One itself has been disbanded due to his expired contract period. The study aims to find out how celebrity worship behaviors and parasocial interactions on the lifestyle of K-Pop fans. The approach used in this study is qualitative with phenomenological methods and uses an interview technique in-depth with one person triangulator and four people informants. The results of this study show that the four informants who are Wannable are in the intermediate stage and level in the conduct of an intense-personal idol in celebrity worship and identification attraction in parasocial interactions. This is because they are still rationally minded and able to position themselves as a fan. It can be known that Indonesian fans are not too fanatic about idols.